Non-communicable disease risk factor patterns among mining industry workers in Papua, Indonesia: longitudinal findings from the Cardiovascular Outcomes in a Papuan Population and Estimation of Risk (COPPER) Study. Issue 10 (31st July 2015) - Rodriguez-Fernandez, Rodrigo; Rahajeng, Ekowati; Viliani, Francesca; Kushadiwijaya, Haripurnomo; Amiya, Rachel M; Bangs, Michael J
Abstract : Objectives: Non-communicable diseases (NCDs) constitute an increasing slice of the global burden of disease, with the South-East Asia region projected to see the highest increase in NCD-related deaths over the next decade. Mining industry employees may be exposed to various factors potentially elevating their NCD risk. This study aimed to assess the distribution and 5-year longitudinal trends of key metabolic NCD risk factors in a cohort of copper–gold mining company workers in Papua, Indonesia. Methods: Metabolic indicators of NCD risk were assessed among employees (15 580 at baseline, 6496 prospectively) of a large copper–gold mining operation in Papua, Indonesia, using routinely collected 5-year medical surveillance data. The study cohort comprised individuals aged 18–68 years employed for ≥1 year during 2008–2013. Assessed risk factors were based on repeat measures of cholesterol, blood glucose, blood pressure and body weight, using WHO criteria. Results: Metabolic risk indicator rates were markedly high and increased significantly from baseline through 5-year follow-up (p<0.001). Adjusting for gender and age, longer duration of employment (≥10 years) predicted raised cholesterol (adjusted OR (AOR)=1.13, p=0.003), raised blood pressure (AOR=1.16, p=0.009) and overweight/obesity (AOR=1.14, p=0.001) at baseline; and persistent raised cholesterol (AOR=1.26, p=0.003), and both incident (AOR=1.33, p=0.014) and persistent raised blood glucose (AOR=1.62, p=0.044) at 3-year follow-up. Conclusions: Individuals employed for longer periods in a mining operations setting in Papua, Indonesia, may face elevated NCD risk through various routes. Workplace health promotion interventions and policies targeting modifiable lifestyle patterns and environmental exposures present an important opportunity to reduce such susceptibilities and mitigate associated health risks.